Enduring Illusions: The Social Organization of Secrecy and Deception - Gibson, David R. (Sociological theory, 2014)
Sociologists theorize that people comply with the dictates of states and other organizations out of self-interest or because of the perceived legitimacy of those in authority. Some organizations, however, are based on lies, or secrets, and it would seem that these should be very short-lived, given how easy it is for the truth to escape. This article lays the foundations of a sociology of deception, focusing on lies and secrets successfully maintained for years or even decades. The ideas of Goffman and Simmel provide a theoretical starting point. Then Bernard Madoff's Ponzi scheme is considered as a case study. Drawing on that and other examples, the article culminates in a theory that distinguishes between barriers to knowing, barriers to asking, barriers to telling, barriers to perceiving, barriers to believing, and barriers to acting. Together, these may counter the natural entropie tendency for information to leak and diffuse, in part because the effectiveness of one sort of barrier may offset imperfections in others.